Influence of Light on Plant–Phyllosphere Interaction - Carvalho, Sofia D.; Castillo, José A. (Frontiers in Plant Science, 2018)
Plant-phyllosphere interactions depend on microbial diversity, the plant host and environmental factors. Light is perceived by plants and by microorganisms and is used as a cue for their interaction. Photoreceptors respond to narrow-bandwidth wavelengths and activate specific internal responses. Light-induced plant responses include changes in hormonal levels, production of secondary metabolites, and release of volatile compounds, which ultimately influence plant-phyllosphere interactions. On the other hand, microorganisms contribute making some essential elements (N, P, Fe) biologically available for plants and producing growth regulators that promote plant growth and fitness. Therefore, light directly or indirectly influences plant-microbe interactions. The usage of light-emitting diodes in plant growth facilities is helping increasing knowledge in the field. This progress will help define light recipes to optimize outputs on plant-phyllosphere communications. This review describes research advancements on light-regulated plant-phyllosphere interactions. The effects of full light spectra and narrow bandwidth-wavelengths from UV to far-red light are discussed.